A Novel Design of Energy-Saving and Prefabricated House System for Rural Area of Northwest China. Issue 1 (June 2021) - Song, Ge; Guo, Liang; Wu, Mengzhuo
Abstract: This research proposes a novel type of rural house design that combines a prefabricated steel frame and EPS cavity blocks as exterior envelop. It has the advantages of low energy consumption, moderate cost, and low assembly difficulty, so as to meet the sustainable development goals of rural areas of China, where status quo of industrialization and economic development is at relatively low level. The article introduces the prefabricated structural features of the system, a semi-industrial construction process, features of refined room modules design based on the size of furniture and residents need at different level, and an automated combination of room modules to house mode with the aid of computer programs to save design time and better meet residents needs. It satisfies China's goal of improving the liveability of rural areas and vigorously developing new prefabricated building systems. Finally, the article looks forward to the future research and development direction.